0637 Associations between Alzheimer's Disease Pathology and the Psychomotor Vigilance Task in Cognitively Unimpaired Adults with and without Obstructive Sleep Apnea. (25th May 2022) - Plante, David; Tran, Kieulinh; Cook, Jesse; Hagen, Erika; Peppard, Paul; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Blennow, Kaj; Zetterberg, Henrik; Carlsson, Cynthia; Johnson, Sterling; Bendlin, Barbara
Abstract: Introduction: Daytime sleepiness is a risk factor for Alzheimer's disease (AD) pathology and is associated with more severe cardiometabolic sequalae in persons with obstructive sleep apnea (OSA). However, limited studies have examined objective measures of decreased alertness in the context of AD. Here, we examined performance on the psychomotor vigilance task (PVT) in relation to AD pathology as indexed by AD biomarkers in cerebrospinal fluid (CSF), among individuals with and without OSA. Methods: Sixty-one cognitively unimpaired adults (39 women), mean age 66.1±7.5 years, enrolled in the Wisconsin Alzheimer's Disease Research Center completed a multifaceted sleep assessment. WatchPAT at-home overnight recordings characterized OSA severity, defined by the apnea-hypopnea index (AHI). Actigraphy determined habitual sleep-wake characteristics. 10-minute PVT measured neurobehavioral alertness. CSF biomarkers were measured using the Roche NeuroToolKit assays (Roche Diagnostics International Ltd, Rotkreuz, Switzerland), an exploratory panel of immunoassays for neurodegeneration. Generalized linear models examined associations between AD biomarkers, AHI, and PVT performance. Primary AD biomarkers of interest were phosphorylated-tau (p-tau) and amyloid-beta (Ab) 42/40 ratio, measured in CSF. The primary PVT variable of interest was the mean response time of the 10% slowest responses, which is associated with daytime sleepiness and default mode network activity. Log transformed PVT and AHI+1 were utilized for analysis. Covariates included age, sex, body mass index, total sleep time, sleep efficiency, APOEe4 status, years of education, AD parental history, biomarker-to-sleep assessment time interval, and Ab42/40 (for p-tau). Results: No significant relationship of AHI or PVT was observed for Ab42/40. In fully adjusted models, a significant AHI*PVT interaction was observed for p-tau (p=0.0003). Specifically, among individuals with OSA (AHI>5/hour; n=24), slower PVT was associated with increased p-tau (b=13.2, p=0.006), an association that was not significant among those without OSA. Conclusion: PVT performance may be an objective measure of sleepiness relevant to AD pathology, particularly among individuals with OSA. Replication and expansion of these findings in larger and longitudinal datasets are indicated. Support (If Any): R03AG063274 and P30-AG062715.